A flame retardant heat-insulating coating and its application in oriented strand board
By using modified aqueous acrylic emulsion and modified vermiculite powder in the coating, the problem of insufficient adhesion and strength of existing coatings is solved, better flame retardant and thermal insulation performance is achieved, and the fire safety of directional particleboard is ensured.
Patent Information
- Application Number
- CN202510065805.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing flame retardant and heat-insulating coatings have insufficient adhesion and strength on directional particleboards, which are prone to fall off, and have poor flame retardant and heat-insulating properties, which cannot effectively prevent fires.
Modified aqueous acrylic emulsion and modified vermiculite powder are used to improve the adhesion and strength of the coating and enhance its flame retardant and thermal insulation properties through graft modification of hydroxyethyl cellulose and surface modification of silane coupling agent.
It significantly improves the adhesion and strength of the coating on the directional particle board, enhances its flame retardant and thermal insulation performance, and can effectively prevent the occurrence of fire.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating compositions, and in particular relates to a flame retardant heat insulating coating and application thereof in oriented strand boards. Background Art
[0002] Oriented strand board is an engineered wood made of long wood chips (shavings) through gluing and pressing. It is characterized by the orderly arrangement of the wood chips, so it has good strength and stability. Oriented strand board is usually used in construction, furniture manufacturing and interior decoration. Compared with traditional plywood, oriented strand board has certain advantages in cost, environmental protection and processing performance. It can be used in building structures such as walls, floors, roofs, etc. It is a common choice in modern building materials, but incompletely processed oriented strand board is not fire-resistant and there are serious safety hazards. In order to reduce the occurrence of fire, it is necessary to coat the surface of the oriented strand board with flame retardant and heat-insulating coating to improve its flame retardant and heat-insulating properties, thereby avoiding the occurrence of fire.
[0003] CN108299970A discloses a method for preparing a highly chlorinated polyethylene fire-retardant coating using amine-loaded vermiculite as a flame retardant. Under high temperature conditions, the vermiculite in the coating expands, and pyrophosphate melamine thermally decomposes to produce inflammable gas to promote foaming, so that the entire system foams and expands to a coating 10-15 times thick, having excellent flame retardancy.
[0004] This patent uses highly chlorinated polyethylene as the film-forming material of the coating. The highly chlorinated polyethylene has a low melt index, and the resulting coating has poor thermal insulation performance and low adhesion to the substrate. Ordinary vermiculite powder is used as the filler of the coating. Ordinary vermiculite powder has poor durability and the prepared coating has low strength. When subjected to friction and external force during daily use, the coating is easily caused to fall off and cannot protect the substrate. Ordinary vermiculite powder has high water absorption, which affects the flame retardant and thermal insulation properties of the coating. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides a flame retardant and heat insulating coating and its application in oriented strand board. The coating has good flame retardant and heat insulating properties, high strength and strong adhesion to the substrate.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A flame retardant heat-insulating coating, comprising a modified water-based acrylic emulsion, a filler, a flame retardant and an additive;
[0008] The mass ratio of the modified waterborne acrylic emulsion, filler, flame retardant and additive is 90-110:10-20:5-15:20-40;
[0009] The filler comprises modified vermiculite powder and glass microspheres, and the mass ratio of the modified vermiculite powder to the glass microspheres is 1.5-2.5:0.5-1.5;
[0010] The particle size of the glass microbeads is 20-50 μm;
[0011] The flame retardant is triethyl phosphate;
[0012] The auxiliary agent includes a thickener, a defoamer, a leveling agent and a dispersant, and the mass ratio of the thickener, the defoamer, the leveling agent and the dispersant is 1:0.9-1.1:0.9-1.1:0.9-1.1;
[0013] The thickener is PEG-150 distearate;
[0014] The defoamer is ethylene oxide;
[0015] The leveling agent is polydimethylsiloxane;
[0016] The dispersant is polyethylene glycol 200.
[0017] The method for preparing the modified water-based acrylic emulsion comprises the steps of preparing the water-based acrylic emulsion and grafting;
[0018] The method for preparing the aqueous acrylic emulsion comprises: adding an emulsifier ammonium sulfate solution into deionized water, mixing evenly, raising the temperature to 70-80° C., adding a pre-emulsified liquid and an initiator diisopropylbenzene peroxide solution dropwise therein at a stirring speed of 300-500 r / min, controlling the dropping speed to be 1-2 g / s, and after the dropping is completed, controlling the reaction temperature to be 70-80° C., the reaction time to be 2-4 h, and after the reaction is completed, obtaining the aqueous acrylic emulsion;
[0019] The mass ratio of the deionized water, the ammonium sulfate solution, the pre-emulsion and the dicumyl peroxide solution is 10-20:2-3:70-100:0.1-1;
[0020] The mass concentration of the dicumyl peroxide solution is 5%-15%;
[0021] The mass concentration of the ammonium sulfate solution is 5%-20%.
[0022] The preparation method of the pre-emulsion is as follows: adding an emulsifier ammonium sulfate solution into deionized water, mixing evenly, adding acrylic acid thereto, reacting at a speed of 500-700 r / min for 1-2 hours to form a stable pre-emulsion;
[0023] In the preparation method of the pre-emulsion, the mass ratio of deionized water, ammonium sulfate solution and acrylic acid is 60-80:1-2:10-20, and the mass concentration of the ammonium sulfate solution is 5%-20%.
[0024] The grafting method comprises adding a hydroxyethyl cellulose solution and an initiator hydrogen peroxide solution into an aqueous acrylic emulsion, raising the reaction temperature to 60-80° C., reacting at a speed of 500-600 r / min for 4-6 hours, and after the stirring reaction is completed, filtering and washing to obtain a modified aqueous acrylic emulsion;
[0025] The mass ratio of the hydroxyethyl cellulose solution, the aqueous acrylic emulsion and the hydrogen peroxide solution is 10-50:90-110:0.1-0.5;
[0026] The mass concentration of the hydroxyethyl cellulose solution is 10%-20%;
[0027] The mass concentration of the hydrogen peroxide solution is 10%-30%.
[0028] The preparation method of the modified vermiculite powder comprises the steps of vermiculite pretreatment and surface modification;
[0029] The method for pretreating vermiculite comprises: crushing and screening the vermiculite ore to obtain vermiculite powder with a particle size of 50-100 μm, adding the vermiculite powder to a sulfuric acid solution for pickling for 1-2 hours to remove impurities and minerals on the surface, filtering, washing and naturally drying after the pickling is completed to obtain the pretreated vermiculite powder;
[0030] The mass ratio of the vermiculite powder to the sulfuric acid solution is 1-5:3-7;
[0031] The mass concentration of the sulfuric acid solution is 10-15%.
[0032] The surface modification method comprises the following steps: placing the pretreated vermiculite powder into deionized water, mixing uniformly to obtain a vermiculite powder dispersion, adding a silane coupling agent into the vermiculite powder dispersion, raising the reaction temperature to 50-70° C., reacting at a speed of 500-600 r / min for 4-6 hours, and after the stirring reaction is completed, filtering and drying to obtain a modified vermiculite powder;
[0033] The mass ratio of the pretreated vermiculite powder, deionized water and silane coupling agent is 10-15:50-75:0.1-0.5;
[0034] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane;
[0035] The preparation method of the flame retardant heat-insulating coating comprises the following steps: adding a modified water-based acrylic emulsion, a filler, a flame retardant and an auxiliary agent into a reaction container, and stirring the mixture at a rotation speed of 300-500 r / min for 1-2 hours to obtain the flame retardant heat-insulating coating.
[0036] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0037] 1. The present invention modifies the water-based acrylic emulsion by adding hydroxyethyl cellulose. At a reaction temperature of 70-80°C, the carboxyl group in acrylic acid combines with the hydroxyl group in hydroxyethyl cellulose to generate monoethylene glycol acrylate (CH-COO-CH2CH2OH). The monoethylene glycol acrylate has good thermal stability and is extremely low in sensitivity to strong light, and can greatly promote the flame retardant and heat-insulating properties of the prepared coating. When the coating is coated on the surface of an oriented strand board and subjected to hot air curing treatment, the double bonds in the monoethylene glycol acrylate in the coating can be chemically cross-linked with the carbonyl group of the active group on the surface of the oriented strand board to form a covalent bond, thereby improving the binding force between the water-based acrylic emulsion and the substrate, and further improving the adhesion of the coating on the oriented strand board.
[0038] 2. The present invention modifies vermiculite powder by modifying the surface of the vermiculite powder with a silane coupling agent. At a reaction temperature of 50-70° C., the silanol groups in the silane coupling agent react with the hydroxyl groups in the vermiculite powder to generate siloxane bonds and water molecules, thereby improving the dispersibility of the vermiculite powder in the organic matrix, reducing its agglomeration phenomenon, improving the dispersibility and stability of the solution, and thus improving the strength of the coating. The siloxane bonds have strong thermal stability and can form a protective silicon oxide film to prevent the further spread of flames, thereby improving the flame retardant and heat insulating properties of the coating.
[0039] 3. The coating prepared by the present invention is coated on the upper surface of an oriented strand board. The adhesion of the coating on the oriented strand board measured by an adhesion tester is 9.9-10.5 MPa, and the adhesion of the coating on the oriented strand board is strong.
[0040] 4. The coating prepared by the present invention is coated on an oriented strand board. After a free-fall hammer test with a heavy hammer, the surface of the oriented strand board has no cracks, peeling or other damage, and the coating has high strength.
[0041] 5. The coating prepared by the present invention is coated on an oriented strand board, and the flame retardant time, flame propagation ratio, mass loss and carbonization volume of the coating are measured to meet the technical requirements stipulated by the state, and the coating has good flame retardant and heat insulation effects. DETAILED DESCRIPTION
[0042] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0043] Example 1
[0044] A flame retardant heat-insulating coating, comprising a modified water-based acrylic emulsion, a filler, a flame retardant and an additive;
[0045] The mass ratio of the modified waterborne acrylic emulsion, filler, flame retardant and additive is 100:15:10:30;
[0046] The filler includes modified vermiculite powder and glass microspheres, and the mass ratio of the modified vermiculite powder to the glass microspheres is 2:1;
[0047] The particle size of the glass microbeads is 30 μm;
[0048] The flame retardant is triethyl phosphate; the auxiliary agent includes a thickener, a defoamer, a leveling agent and a dispersant, and the mass ratio of the thickener, the defoamer, the leveling agent and the dispersant is 1:1:1:1;
[0049] The thickener is PEG-150 distearate;
[0050] The defoamer is ethylene oxide;
[0051] The leveling agent is polydimethylsiloxane;
[0052] The dispersant is polyethylene glycol 200.
[0053] The preparation method of the modified waterborne acrylic emulsion is as follows:
[0054] (1) Preparation of water-based acrylic emulsion
[0055] Deionized water and an emulsifier ammonium sulfate solution were added to the reactor, and after being mixed evenly, the temperature was raised to 75°C. The pre-emulsified liquid and the initiator diisopropylbenzene peroxide solution were added dropwise at a stirring speed of 400 r / min, and the dropping speed was controlled to be 1.5 g / s. After the dropping was completed, the reaction temperature was controlled to be 75°C, and the reaction time was 3 h. After the reaction was completed, a water-based acrylic emulsion was obtained;
[0056] The mass ratio of the deionized water, the ammonium sulfate solution, the pre-emulsion and the dicumyl peroxide solution is 15:2.5:85:0.5;
[0057] The mass concentration of the dicumyl peroxide solution is 10%;
[0058] The mass concentration of the ammonium sulfate solution is 15%;
[0059] The preparation method of the pre-emulsion is as follows: adding an emulsifier ammonium sulfate solution into deionized water, mixing evenly, adding acrylic acid thereto, reacting at a speed of 600 r / min for 1.5 hours to form a stable pre-emulsion;
[0060] In the preparation method of the pre-emulsion, the mass ratio of deionized water, ammonium sulfate solution and acrylic acid is 70:1.5:15, and the mass concentration of the ammonium sulfate solution is 15%.
[0061] (2) Grafting
[0062] Adding hydroxyethyl cellulose solution and initiator hydrogen peroxide solution into a reaction container containing water-based acrylic emulsion, raising the reaction temperature to 70°C, reacting at a speed of 550 r / min for 5 hours, and after the stirring reaction is completed, filtering and washing to obtain a modified water-based acrylic emulsion;
[0063] The mass ratio of the hydroxyethyl cellulose solution, the aqueous acrylic emulsion and the hydrogen peroxide solution is 30:100:0.3;
[0064] The mass concentration of the hydroxyethyl cellulose solution is 15%;
[0065] The mass concentration of the hydrogen peroxide solution is 20%.
[0066] The preparation method of the modified vermiculite powder is as follows:
[0067] (1) Vermiculite pretreatment
[0068] The vermiculite ore is crushed and sieved to obtain vermiculite powder with a particle size of 80 μm, and the vermiculite powder is added to a reaction container filled with sulfuric acid solution for pickling for 1.5 hours to remove impurities and minerals on the surface. After the pickling is completed, the vermiculite powder is filtered, washed and naturally dried to obtain pretreated vermiculite powder;
[0069] The mass ratio of the vermiculite powder to the sulfuric acid solution is 3:5;
[0070] The mass concentration of the sulfuric acid solution is 13%.
[0071] (2) Surface modification
[0072] The pretreated vermiculite powder is put into deionized water and mixed evenly to obtain a vermiculite powder dispersion, a silane coupling agent is added to a reaction container containing the vermiculite powder dispersion, the reaction temperature is controlled to be 60° C., and the reaction is carried out at a speed of 550 r / min for 5 hours. After the reaction is completed, the modified vermiculite powder is obtained by filtering and drying.
[0073] The mass ratio of the pretreated vermiculite powder, deionized water and silane coupling agent is 13:63:0.3;
[0074] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane;
[0075] The preparation method of the flame retardant heat-insulating coating comprises the following steps: adding a modified waterborne acrylic emulsion, a filler, a flame retardant and an auxiliary agent into a reaction container, stirring the mixture at a speed of 400 r / min for 1.5 hours, and obtaining the flame retardant heat-insulating coating.
[0076] Example 2
[0077] A flame retardant heat-insulating coating, comprising a modified water-based acrylic emulsion, a filler, a flame retardant and an additive;
[0078] The mass ratio of the modified waterborne acrylic emulsion, filler, flame retardant and additive is 90:10:5:20;
[0079] The filler includes modified vermiculite powder and glass microspheres, and the mass ratio of the modified vermiculite powder to the glass microspheres is 1.5:0.5;
[0080] The particle size of the glass microbeads is 20 μm;
[0081] The flame retardant is triethyl phosphate; the auxiliary agent includes a thickener, a defoamer, a leveling agent and a dispersant, and the mass ratio of the thickener, the defoamer, the leveling agent and the dispersant is 1:0.9:0.9:0.9;
[0082] The thickener is PEG-150 distearate;
[0083] The defoamer is ethylene oxide;
[0084] The leveling agent is polydimethylsiloxane;
[0085] The dispersant is polyethylene glycol 200.
[0086] The preparation method of the modified waterborne acrylic emulsion is as follows:
[0087] (1) Preparation of water-based acrylic emulsion
[0088] Deionized water and an emulsifier ammonium sulfate solution were added to the reactor, and after being mixed evenly, the temperature was raised to 70°C. The pre-emulsified liquid and the initiator diisopropylbenzene peroxide solution were added dropwise at a stirring speed of 300 r / min, and the dropping speed was controlled to be 1 g / s. After the dropping was completed, the reaction temperature was controlled to be 70°C, and the reaction time was 2 h. After the reaction was completed, a water-based acrylic emulsion was obtained;
[0089] The mass ratio of the deionized water, the ammonium sulfate solution, the pre-emulsion and the dicumyl peroxide solution is 10:2:70:0.1;
[0090] The mass concentration of the ammonium sulfate solution is 5%;
[0091] The mass concentration of the dicumyl peroxide solution is 5%;
[0092] The preparation method of the pre-emulsion is as follows: adding an emulsifier ammonium sulfate solution into deionized water, mixing evenly, adding acrylic acid thereto, reacting at a speed of 500 r / min for 1 hour, and forming a stable pre-emulsion;
[0093] In the method for preparing the pre-emulsion, the mass ratio of deionized water, ammonium sulfate solution and acrylic acid is 60:1:10, and the mass concentration of the ammonium sulfate solution is 5%.
[0094] (2) Grafting
[0095] Adding the hydroxyethyl cellulose solution and the initiator hydrogen peroxide solution into a reaction container containing the aqueous acrylic emulsion, raising the reaction temperature to 60° C., reacting at a speed of 500 r / min for 4 hours, and after the stirring reaction is completed, filtering and washing to obtain a modified aqueous acrylic emulsion;
[0096] The mass ratio of the hydroxyethyl cellulose solution, the aqueous acrylic emulsion and the hydrogen peroxide solution is 10:90:0.1;
[0097] The mass concentration of the hydroxyethyl cellulose solution is 10%;
[0098] The mass concentration of the hydrogen peroxide solution is 10%.
[0099] The preparation method of the modified vermiculite powder is as follows:
[0100] (1) Vermiculite pretreatment
[0101] The vermiculite ore is crushed and sieved to obtain vermiculite powder with a particle size of 50 μm, and the vermiculite powder is added to a reaction container filled with sulfuric acid solution for pickling for 1 hour to remove impurities and minerals on the surface. After the pickling is completed, the vermiculite powder is filtered, washed and naturally dried to obtain pretreated vermiculite powder;
[0102] The mass ratio of the vermiculite powder to the sulfuric acid solution is 1:3;
[0103] The mass concentration of the sulfuric acid solution is 10%.
[0104] (2) Surface modification
[0105] The pretreated vermiculite powder is put into deionized water and mixed evenly to obtain a vermiculite powder dispersion, a silane coupling agent is added to a reaction container containing the vermiculite powder dispersion, the reaction temperature is controlled to be 50° C., the reaction is carried out at a speed of 500 r / min for 4 hours, and after the stirring reaction is completed, the mixture is filtered and dried to obtain a modified vermiculite powder;
[0106] The mass ratio of the pretreated vermiculite powder, deionized water and silane coupling agent is 10:50:0.1;
[0107] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane;
[0108] The preparation method of the flame retardant heat-insulating coating comprises the following steps: adding a modified water-based acrylic emulsion, a filler, a flame retardant and an auxiliary agent into a reaction container, stirring the mixture at a rotation speed of 300 r / min for 1 hour, and obtaining the flame retardant heat-insulating coating.
[0109] Example 3
[0110] A flame retardant heat-insulating coating, comprising a modified water-based acrylic emulsion, a filler, a flame retardant and an additive;
[0111] The mass ratio of the modified waterborne acrylic emulsion, filler, flame retardant and additive is 110:20:15:40;
[0112] The filler includes modified vermiculite powder and glass microspheres, and the mass ratio of the modified vermiculite powder to the glass microspheres is 2.5:1.5;
[0113] The particle size of the glass microbeads is 50 μm;
[0114] The flame retardant is triethyl phosphate;
[0115] The auxiliary agent includes a thickener, a defoamer, a leveling agent and a dispersant, and the mass ratio of the thickener, the defoamer, the leveling agent and the dispersant is 1:1.1:1.1:1.1;
[0116] The thickener is PEG-150 distearate;
[0117] The defoamer is ethylene oxide;
[0118] The leveling agent is polydimethylsiloxane;
[0119] The dispersant is polyethylene glycol 200.
[0120] The preparation method of the modified waterborne acrylic emulsion is as follows:
[0121] (1) Preparation of water-based acrylic emulsion
[0122] Deionized water and an emulsifier ammonium sulfate solution were added to the reactor, and after being mixed evenly, the temperature was raised to 80°C. The pre-emulsified liquid and the initiator diisopropylbenzene peroxide solution were added dropwise at a stirring speed of 500 r / min, and the dropping speed was controlled to be 2 g / s. After the dropping was completed, the reaction temperature was controlled to be 80°C, and the reaction time was 4 h. After the reaction was completed, a water-based acrylic emulsion was obtained;
[0123] The mass ratio of the deionized water, ammonium sulfate solution, pre-emulsion and dicumyl peroxide solution is 20:3:100:1;
[0124] The mass concentration of the ammonium sulfate solution is 20%;
[0125] The mass concentration of the dicumyl peroxide solution is 15%;
[0126] The preparation method of the pre-emulsion is as follows: adding an emulsifier ammonium sulfate solution into deionized water, mixing evenly, adding acrylic acid thereto, reacting at a speed of 700 r / min for 2 hours, and forming a stable pre-emulsion;
[0127] In the preparation method of the pre-emulsion, the mass ratio of deionized water, ammonium sulfate solution and acrylic acid is 80:2:20, and the mass concentration of the ammonium sulfate solution is 20%.
[0128] (2) Grafting
[0129] The hydroxyethyl cellulose solution and the initiator hydrogen peroxide solution are added to a reaction container containing the aqueous acrylic emulsion, the reaction temperature is controlled to be 80° C., the reaction is carried out at a speed of 600 r / min for 6 hours, and after the stirring reaction is completed, the modified aqueous acrylic emulsion is obtained by filtering and washing.
[0130] The mass ratio of the hydroxyethyl cellulose solution, the aqueous acrylic emulsion and the hydrogen peroxide solution is 50:110:0.5;
[0131] The mass concentration of the hydroxyethyl cellulose solution is 20%;
[0132] The mass concentration of the hydrogen peroxide solution is 30%.
[0133] The preparation method of the modified vermiculite powder is as follows:
[0134] (1) Vermiculite pretreatment
[0135] The vermiculite ore is crushed and sieved to obtain vermiculite powder with a particle size of 80 μm, and the vermiculite powder is added to a reaction container filled with sulfuric acid solution for pickling for 2 hours to remove impurities and minerals on the surface. After the pickling is completed, the vermiculite powder is filtered, washed and naturally dried to obtain pretreated vermiculite powder;
[0136] The mass ratio of the vermiculite powder to the sulfuric acid solution is 5:7;
[0137] The mass concentration of the sulfuric acid solution is 15%.
[0138] (2) Surface modification
[0139] The pretreated vermiculite powder is put into deionized water and mixed evenly to obtain a vermiculite powder dispersion, a silane coupling agent is added to a reaction container containing the vermiculite powder dispersion, the reaction temperature is increased to 70° C., and the reaction is carried out at a speed of 600 r / min for 6 hours. After the stirring reaction is completed, the mixture is filtered and dried to obtain a modified vermiculite powder;
[0140] The mass ratio of the pretreated vermiculite powder, deionized water and silane coupling agent is 15:75:0.5;
[0141] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane;
[0142] The preparation method of the flame retardant heat-insulating coating comprises the following steps: adding a modified waterborne acrylic emulsion, a filler, a flame retardant and an auxiliary agent into a reaction container, stirring the mixture at a rotation speed of 500 r / min for 2 hours, and obtaining the flame retardant heat-insulating coating.
[0143] Example 4 Application of a flame retardant heat insulation coating in oriented strand board
[0144] The flame retardant heat-insulating coating is applied to the upper surface of the oriented strand board, and after coating, it is dried by hot air at 120° C. for 20 minutes. The coating film thickness after curing is 100 μm, and the oriented strand board coated with the flame retardant heat-insulating coating is obtained.
[0145] Comparative Example 1
[0146] Based on Example 1, the change is that the grafting step in the preparation method of the modified water-based acrylic emulsion is omitted, and in the preparation method of the flame retardant and thermal insulation coating, the water-based acrylic emulsion is used instead of the modified water-based acrylic emulsion, and the other operations are the same.
[0147] Comparative Example 2
[0148] Based on Example 1, the changes are that the vermiculite powder is not modified, the surface modification step in the preparation method of the modified vermiculite powder is omitted, and in the preparation method of the flame retardant and thermal insulation coating, the pretreated vermiculite powder is used instead of the modified vermiculite powder, and the other operations are the same.
[0149] The coatings prepared in Examples 1-3 and Comparative Examples 1-2 were used according to the method of Example 4 to prepare oriented strand boards coated with the coatings, and the following experiments were carried out.
[0150] Test Example 1 Adhesion Performance Test
[0151] Prepare the oriented strand board coated with the coatings described in Examples 1-3 and Comparative Examples 1-2, and then place the adhesion tester BYK on the surface of the oriented strand board, with the contact area uniformly set to 50 mm 2, use the tester to gradually increase the pulling force until the coating separates from the substrate. The coating adhesion calculation formula is: AF=F / A;
[0152] In the above formula, AF is the adhesion force (MPa), A is the contact area (mm 2 ), F is the pulling force (N);
[0153] The test results are shown in Table 1:
[0154] Table 1 Adhesion test results of coatings
[0155]
[0156] Test Example 2 Strength Performance Test of Coating
[0157] Oriented strand boards coated with the coatings of Examples 1-3 and Comparative Examples 1-2 were prepared and fixed in the fixture of a drop hammer tester. A 500 g drop hammer was used to drop the drop hammer freely from a height of 100 cm to hit the center of the test board. The data of each drop hammer was recorded. The test results are shown in Table 2:
[0158] Table 2 Strength test results of coatings
[0159]
[0160] Test Example 3 Flame retardant and heat insulation performance test of coating
[0161] The flame retardant and heat-insulating coatings prepared in Examples 1-3 and Comparative Examples 1-2 were tested for flame retardant and heat-insulating properties according to the standard GB / T 12441-2005 "Surface Fire Retardant Coatings". The oriented strand boards coated with the coatings in Examples 1-3 and Comparative Examples 1-2 were cut according to the A3B3C3 regulations in the standard. The test results are shown in Table 3:
[0162] Table 3 Flame retardant and heat insulation performance test results
[0163]
[0164] It can be seen from the test results of Experimental Example 1 that the adhesion of the coating can be improved by adding hydroxyethyl cellulose to the aqueous acrylic emulsion for grafting modification. Comparative Example 1 omits the grafting step in the preparation method of the modified aqueous acrylic emulsion and uses ordinary aqueous acrylic emulsion as the film-forming substance of the coating, and the adhesion of the prepared coating is weak.
[0165] It can be seen from the test results of Experimental Example 2 that the strength of the coating can be improved by adding a silane coupling agent to the vermiculite to modify the surface of the vermiculite powder. In Comparative Example 2, the vermiculite powder was not modified and ordinary vermiculite powder was used as a filler. The prepared coating film had fine cracks and the strength of the coating was poor.
[0166] It can be seen from the test results of Experimental Example 3 that the flame retardant and thermal insulation coating prepared in Example 1 has the best performance, and the flame retardant time, flame propagation ratio, mass loss and carbonization volume of the coatings prepared in Comparative Examples 1 and 2 are significantly lower than the various performance indicators of the coatings prepared in Examples 1-3, and the flame retardant and thermal insulation properties of the coatings prepared in Comparative Examples 1 and 2 are poor.
[0167] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0168] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A flame retardant and heat insulating coating, characterized in that: The flame retardant heat-insulating coating comprises a modified water-based acrylic emulsion, a filler, a flame retardant and an additive; The method for preparing the modified waterborne acrylic emulsion comprises a grafting step; The grafting method comprises adding a hydroxyethyl cellulose solution and an initiator hydrogen peroxide solution into an aqueous acrylic emulsion, controlling the reaction temperature to be 60-80° C., reacting for 4-6 hours, and filtering and washing after the reaction to obtain a modified aqueous acrylic emulsion; In the grafting method, the mass ratio of hydroxyethyl cellulose solution, aqueous acrylic emulsion and hydrogen peroxide solution is 10-50:90-110:0.1-0.5; the mass concentration of the hydroxyethyl cellulose solution is 10%-20%; The mass concentration of the hydrogen peroxide solution is 10%-30%; The filler includes modified vermiculite powder and glass microspheres; The preparation method of the modified vermiculite powder comprises a surface modification step; The surface modification method comprises the following steps: placing the pretreated vermiculite powder into deionized water, mixing uniformly to obtain a vermiculite powder dispersion, adding a silane coupling agent into the vermiculite powder dispersion, controlling the reaction temperature to be 50-70° C., reacting for 4-6 hours, filtering and drying after the reaction is completed to obtain modified vermiculite powder.
2. The flame retardant and heat insulating coating according to claim 1, characterized in that: The method for preparing the modified water-based acrylic emulsion comprises the steps of preparing the water-based acrylic emulsion; The method for preparing the aqueous acrylic emulsion comprises: adding an emulsifier ammonium sulfate solution into deionized water, mixing uniformly, raising the temperature to 70-80° C., and dripping a pre-emulsified liquid and an initiator diisopropylbenzene peroxide solution into the deionized water at a dripping speed of 1-2 g / s. After the dripping is completed, the reaction temperature is controlled to be 70-80° C., the reaction time is 2-4 hours, and after the reaction is completed, the aqueous acrylic emulsion is obtained. In the method for preparing the aqueous acrylic emulsion, the mass ratio of deionized water, ammonium sulfate solution, pre-emulsion solution and dicumyl peroxide solution is 10-20:2-3:70-100:0.1-1; The mass concentration of the dicumyl peroxide solution is 5%-15%; the mass concentration of the ammonium sulfate solution is 5%-20%.
3. The flame retardant and heat insulating coating according to claim 2, characterized in that: The preparation method of the pre-emulsion is to add an emulsifier ammonium sulfate solution into deionized water, mix well, add acrylic acid thereto, react for 1-2 hours, and form a stable pre-emulsion; In the preparation method of the pre-emulsion, the mass ratio of deionized water, ammonium sulfate solution and acrylic acid is 60-80:1-2:10-20, and the mass concentration of the ammonium sulfate solution is 5%-20%.
4. The flame retardant and heat insulating coating according to claim 1, characterized in that: The method for preparing the modified vermiculite powder comprises a vermiculite pretreatment step; The method for pretreating vermiculite is as follows: the vermiculite ore is crushed and sieved, and then added to a sulfuric acid solution for pickling for 1-2 hours. After the pickling is completed, the vermiculite ore is filtered, washed and naturally dried to obtain pretreated vermiculite powder; In the vermiculite pretreatment method, the mass ratio of vermiculite powder to sulfuric acid solution is 1-5:3-7; and the mass concentration of sulfuric acid solution is 10-15%.
5. The flame retardant and heat insulating coating according to claim 1, characterized in that: In the surface modification method, the mass ratio of the pretreated vermiculite powder, deionized water and silane coupling agent is 10-15:50-75:0.1-0.5; The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
6. The flame retardant and heat insulating coating according to claim 1, characterized in that: The preparation method of the flame retardant heat-insulating coating comprises the following steps: adding a modified waterborne acrylic emulsion, a filler, a flame retardant and an auxiliary agent into a reaction container, stirring the mixture at a rotation speed of 300-500 r / min for 1-2 hours, and obtaining the flame retardant heat-insulating coating.
7. The flame retardant and heat insulating coating according to claim 1, characterized in that: The mass ratio of the modified waterborne acrylic emulsion, filler, flame retardant and additive is 90-110:10-20:5-15:20-40; The mass ratio of modified vermiculite powder to glass microspheres in the filler is 1.5-2.5:0.5-1.5; The particle size of the glass microbeads is 20-50 μm; and the flame retardant is triethyl phosphate.
8. The flame retardant and heat insulating coating according to claim 1, characterized in that: The auxiliary agent includes a thickener, a defoamer, a leveling agent and a dispersant, and the mass ratio of the thickener, the defoamer, the leveling agent and the dispersant is 1:0.9-1.1:0.9-1.1:0.9-1.1; The thickener is PEG-150 distearate; the defoamer is ethylene oxide; the leveling agent is polydimethylsiloxane; The dispersant is polyethylene glycol 200.
9. Use of the flame retardant and heat insulating coating according to any one of claims 1 to 8 in oriented strand board.
Citation Information
Patent Citations
Method for preparing high chlorinated polyethylene fireproof paint by using amine loaded vermiculite as flame retardant
CN108299970A
Waterborne epoxy anticorrosive paint with modified vermiculite being used as functional filler and preparation method thereof
CN104004440A
Aqueous environmentally-friendly heat-insulating flame-retardant coating material and preparation method thereof
CN109694630A